Early career biomedical grantsmanship self‐efficacy: validation of an abbreviated self‐assessment tool. Issue 1 (5th December 2018) - Harwood, Eileen M.; Jones, Amy R.; Erickson, Darin; Buchwald, Dedra; Johnson‐Hemming, Japera; Jones, Harlan P.; Manson, Spero; McGee, Richard; Smith, Ann; Steer, Clifford J.; Vishwanatha, Jamboor K.; Weber‐Main, Anne M.; et al.
Abstract: A hallmark of success for early career biomedical researchers is the acquisition of research funding. There are marked disparities among principal investigators who submit grants and the likelihood of receiving national funding. The National Research Mentoring Network was funded by the National Institutes of Health to diversify the biomedical research workforce and included grantsmanship training for early career researchers. Self‐efficacy in developing research grant applications is significantly improved over time with training and experience. We created a 19‐item self‐efficacy assessment inventory. Our aims were to confirm the internal consistency of a three‐factor solution for grantsmanship confidence and to test the likelihood that self‐efficacy influences grant proposal submission timing. We gathered data from 190 diverse biomedical trainees who completed NRMN grantsmanship training between August 2015 and June 2017. Findings revealed high internal consistency for items in each of three factors. There was a statistically significant association between self‐efficacy mean scores and grant submission timing predicting that, for every one‐point increase in the mean score, the odds of submitting a grant 6 months post‐training increased by 69%. An abbreviated inventory of grantsmanship skills self‐efficacy is a promising tool for monitoring changes over time in early career researchers and for promoting tailored grantsmanship interventions.